2022
DOI: 10.1101/2022.03.11.22272140
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High vaccine effectiveness against severe Covid-19 in the elderly in Finland before and after the emergence of Omicron

Abstract: Background. The elderly are highly vulnerable to severe Covid-19. Waning immunity and emergence of Omicron have caused concerns about reduced effectiveness of Covid-19 vaccines. The objective was to estimate vaccine effectiveness (VE) against severe Covid-19 among the elderly. Methods. This nationwide, register-based cohort study included all residents aged 70 years and over in Finland. The follow-up started on December 27, 2020, and ended on February 19, 2022. The study outcomes were Covid-19-related hospit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
1
12
1
Order By: Relevance
“…In contrast to our results, waning of protection against Omicron-related COVID-19 hospitalisation with time since vaccination with either two or three doses was reported by some [ 7 , 11 , 12 ], while strong and durable protection after the second mRNA dose and even more robust protection after a booster dose was also reported by a recent study from Qatar [ 13 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, waning of protection against Omicron-related COVID-19 hospitalisation with time since vaccination with either two or three doses was reported by some [ 7 , 11 , 12 ], while strong and durable protection after the second mRNA dose and even more robust protection after a booster dose was also reported by a recent study from Qatar [ 13 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Understanding how much longer the high protection against Omicron-related SARI COVID-19 hospitalisation will last, will only be possible in the future, when the number of people vaccinated with the third dose more than 6 months ago will accumulate. Similar results with respect to protection against hospitalisation due to Omicron-related COVID-19 for elderly individuals (aged 70 years and older) were reported from Finland (VE of 91% and 76%, 14–90 and 91–180 days after second dose, and 95%, 14–60 days after third dose) [ 11 ].…”
Section: Discussionsupporting
confidence: 80%
“…Among the 121 studies under full-text review, 98 studies were excluded. Eventually, 23 studies (including 13 published articles and 10 preprints) were included in this meta-analysis based on the inclusion criteria [ 14 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10]12,13,[15][16][17][18] In addition, this study provides new information on the utilisation of the inactivated vaccine BBIBP-CorV, the viral vector vaccine rAd26-rAd5, and heterologous primary schemes, which was previously quite scarce. 19 After realizing that ChAdOx1 nCoV-19 administration was associated with increased risk of thrombosis with thrombocytopenia syndrome, some European Union Member…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported with heterologous boosting after the administration of primary schemes with the inactivated vaccine Sinovac and the vectored vaccines Ad26.COV2-S and ChAdOx1 nCoV-19. 13,15,[17][18][19][20] Although our results are the first to report protection in a real-life setting, they are in line with in vitro studies: Argentinian researchers found that a heterologous booster with ChAdOx1 nCoV-19, rAd26-rAd5, or BNT162b2 vaccines markedly increased the neutralising activity against the Omicron variant and was maintained up to 90 days in older people with primary schemes of BBIBP-CorV. 8 Furthermore, researchers from Bahrein and Serbia reported that heterologous 11 boosting with Pfizer-BioNTech after administering a primary scheme with rAd26-rAd5 yielded higher levels of antibodies than homologous boosting.…”
Section: Discussionmentioning
confidence: 99%